ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI KURS DOLLAR AMERIKA PADA MASA SEBELUM DAN SAAT PANDEMI COVID-19 DI INDONESIA - Mahendra, I Wayan Yoga Praditya; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 10 (2022): vol.11.10. OKTOBER 2022 [3701 - 4009], 2022)
The economic life of a country cannot be separated from the state of the foreign economy. The purpose of this study is to analyze the influence of the Covid-19 pandemic, interest rates, inflation, and net exports simultaneously and partially on the US dollar exchange rate. This research was conducted in Indonesia. The type of data used is quantitative in the form of associative. Data collection methods using indirect observation. This study uses a non-participant observation method which is calculated by taking 15 months before the pandemic (December 2018 – February 2020), and 15 months during the pandemic (March 2020 – May 2021) so that the sample size in this study is 30. data analysis used in this research is multiple linear regression analysis. The results of data analysis show that the results of simultaneous testing show that the Covid-19 pandemic, interest rates, inflation, and net exports simultaneously have a significant effect on the US dollar exchange rate. The Covid-19 pandemic and inflation partially had a positive and significant effect on the US dollar exchange rate, while interest rates and net exports partially had a positive but not significant effect on the US dollar exchange rate. It is hoped that the government can make policies and become one of the evaluation materials to maintain exchange rate stability. Keywords : Covid-19, Inflation, Interest Rate.Net Export,Exchange Rate